The ideas of man and woman in Renaissance France : print, rhetoric, and law - Warner, Lyndan (Women and gender in the early modern world., 2011)
The Ideas of Man and Woman in Renaissance France provides the first comprehensive comparison of the printed debates over the superiority or inferiority of woman - the Querelle des femmes - and the dignity and misery of man, revealing the striking overlap between them as they evolved into the 1600s. Drawing on probate inventories, court registers and published lawyers' pleadings, Lyndan Warner traces these intertwined ideas from author to bookseller to reader.